Increasing Knowledge, Attitudes and Behavior of the Community - Triana, Hanni; Natalia, Lidya; Sinaga, Saurmian; Sarce, Sari; Ngadiran, Antonius; Yuliani, Yuliani; Widiastuti, Yuliati; Ardayani, Tri (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
This service program aims to increase public knowledge about mental health, stunting in infants and toddlers, TB, scabies, high risk for pregnant women and the importance of healthy living by not littering.  The method of community service is carried out by means of counseling, lectures, and questions and answers. The media used are televisions and laptops to display material in the form of power points. The data analysis technique carried out is qualitative descriptive analysis. The data collection techniques used are observation and documentation. This service activity was carried out in Babakan Ciparay District, one of the sub-districts in the city of Bandung, especially in RW 06. This service was held in September 2022.Based on the results of community service activities, it can be seen that the knowledge of community service participants increases after counseling is given, this is evidenced by the results of the evaluation carried out for 2 days. The results of the evaluation can be seen from the behavior of the community will maintain better health.